2014
DOI: 10.2147/dddt.s67518
|View full text |Cite
|
Sign up to set email alerts
|

Time and dose relationships between schisandrin B- and schisandrae fructus oil-induced hepatotoxicity and the associated elevations in hepatic and serum triglyceride levels in mice

Abstract: BackgroundSchisandrin B (Sch B), a dibenzocyclooctadiene compound, is isolated from schisandrae fructus (SF). This study was conducted to compare the time- and dose-response between Sch B- and SF oil (SFO)-induced changes in hepatic and serum parameters in mice.MethodsInstitute of Cancer Research (ICR) mice were given a single oral dose of Sch B (0.125–2 g/kg) or SFO (0.3–5 g/kg). Serum alanine aminotransferase (ALT) activity, hepatic malondialdehyde, and triglyceride (TG) levels were measured at increasing ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Most of the previous studies reported that the SC active lignans had hepatoprotective effect against many kinds of liver diseases. However, it was recently revealed that schisandrin B and schisandrae fructus oil could induce hepatotoxicity associated with elevations in hepatic and serum triglyceride levels in mice (Zhang et al, 2014 ). In addition, it was found that SC lignans exhibited inhibition or induction effects on CYP450s, the most important drug metabolism enzymes, causing herbal-drug interaction which might affect the drug therapy or safety (Wang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the previous studies reported that the SC active lignans had hepatoprotective effect against many kinds of liver diseases. However, it was recently revealed that schisandrin B and schisandrae fructus oil could induce hepatotoxicity associated with elevations in hepatic and serum triglyceride levels in mice (Zhang et al, 2014 ). In addition, it was found that SC lignans exhibited inhibition or induction effects on CYP450s, the most important drug metabolism enzymes, causing herbal-drug interaction which might affect the drug therapy or safety (Wang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many pharmacological studies revealed that SC and schisandra lignans, the major effective components, showed various beneficial biological activities including hepatoprotection against viral and various hepatotoxins, tranquilization, hypnogenesis, anticonvulsive and neuro-protective effects, and so on (Lu and Liu, 1992 ; Fujihashi et al, 1995 ; Zhu et al, 2016 ; Szopa et al, 2017 ). However, it was recently reported that schisandrin B and schisandrae fructus oil could elevate hepatic and serum triglyceride levels, heighten serum alanine aminotransferase (ALT) activity, and eventually induce hepatotoxicity (hypertriglyceridemia, hepatomegaly and liver damage) in mice (Zhang et al, 2014 ). SC extracts exhibited inhibitive or inductive effects on rat hepatic cytochrome P450 (CYP450) enzymes and caused herb-drug interaction mediated by CYP450s (Wang et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study showed that fenofibrate, a widely prescribed TG-lowering agent, could eliminate Sch B- and Sch oil-induced hypertriglyceridemia, hepatic steatosis, and liver injury [20, 31]. It has been demonstrated that Sch B caused hepatotoxicity (increase in serum ALT activity [19] via PI3K/AKt/mtOR signaling pathway in our previous study [32]. We consider that Sch B-induced hypertriglyceridemia and hepatic steatosis resulted from the lipolysis (decrease in adipocyte size and increase in serum NEFA) and exogenous sources (increase in serum Apo B48).…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of Schisandrae Fructus and its active components is more popular in China and other Asian countries which are strongly influenced by the practice of Chinese medicine. Previous studies from our laboratory have demonstrated that Sch B treatment increased serum and hepatic TG levels, serum alanine aminotransferase (ALT) activity and hepatic mass in mice, suggestive of a mouse model of hypertriglyceridemia combined with hepatic steatosis and injury [1921]. It is well known that TG in bloodstream is derived from exogenous (dietary sources) and endogenous (synthesis in liver using fatty acids) pathways.…”
Section: Introductionmentioning
confidence: 99%
“…FSC has previously been reported to have a wide spectrum of biological effects, including protecting against chemically and virally induced hepatic injury [ 13 , 14 ], improving insulin sensitivity [ 15 ], protecting against oxidative damage [ 16 ], producing sedative–hypnotic activity and anti-inflammatory effects [ 17 , 18 ]. Our previous works have demonstrated that FSC extract and FSC-related compounds significantly altered lipid metabolism in mice [ 19 23 ]. In the present study, we endeavored to evaluate the effects of dietary supplementation with FSC seed (FSC-S) and the post-ethanol extraction residue of FSC-S (FSC-SpEt) on serum and hepatic lipid/glucose (GLU) contents in both normal diet-fed (ND) and high cholesterol/bile salt diet-fed (HCBD) mice, an animal model of hypercholesterolemia (HCL).…”
Section: Introductionmentioning
confidence: 99%